Does Governance Explain the Variation in Growth of the Regional Comprehensive Economic Partnership (RCEP) Bloc Countries? An Econometric Analysis - Bajit, Elizabeth (Archīum Ateneo, 2021)
This study examined the impact of governance on the economic growth of 16 countries consisting of the ASEAN 10 and the six countries which have Free Trade Agreements with the ASEAN 10 covering the period 2002 to 2014. An extended Solow (1956) growth model was used with governance as additional determinant. The data were analyzed using the Generalized Method of Moments (GMM) estimation. Given the opposing theories and mixed evidence in the existing literature regarding the relationship between governance and economic growth, the findings confirmed the hypotheses that countries which have better governance quality measured in terms government effectiveness, regulatory quality, rule of law, political stability and absence of violence/terrorism, and control of corruption have higher economic growth. Contrary to the hypothesis that countries with better governance quality measured in voice and accountability have higher economic growth, this study shows that voice and accountability has a negative effect on economic growth. Although recession has a negative effect on governance-growth nexus, the net effects of government effectiveness, regulatory quality, rule of law, political stability and absence of violence, and control of corruption on economic growth are positive, while the net effect of voice and accountability is negative. The study shows that governance affects economic growth by improving the production efficiency and through enhancing physical capital accumulation.